A multi-approach inventory of the blue carbon stocks of Posidonia oceanica seagrass meadows: Large scale application in Calvi Bay (Corsica, NW Mediterranean). (January 2023) - Leduc, Michèle; Abadie, Arnaud; Viala, Christophe; Bouchard, Alban; Iborra, Laura; Fontaine, Quentin; Lepoint, Gilles; Marengo, Michel; Pergent, Gérard; Gobert, Sylvie; Lejeune, Pierre; Monnier, Briac
Abstract: In Mediterranean, Posidonia oceanica develops a belowground complex structure ('matte') able to store large amounts of carbon over thousands of years. The inventory of blue carbon stocks requires the coupling of mapping techniques and in situ sediment sampling to assess the size and the variability of these stocks. This study aims to quantify the organic (Corg ) and inorganic (Cinorg ) carbon stocks in the P. oceanica matte of the Calvi Bay (Corsica) using sub-bottom profiler imagery and biogeochemical analysis of sediment cores. The matte thicknesses map (average ± SD: 2.2 m ± 0.4 m) coupled with marine benthic habitat cartography allows to estimate matte volume at 12 473 352 m 3 . The cumulative stocks were assessed at 20.2–50.3 kg Corg m −2 and 26.6–58.7 kg Cinorg m −2 within the first meter of depth on matte (3632 ± 486 cal yr BP). The data contributed to estimate the overall carbon stocks at 389 994 t Corg and 615 558 t Cinorg, offering a new insight of the heterogeneity of blue carbon stocks in seagrass meadows. Variability of carbon storage capacity of matte influenced by substrate is discussed.